2020
DOI: 10.1002/pen.25330
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Service Life and Electrical Insulation Properties of Polymeric Cables With the Optimum Content of Aromatic Voltage Stabilizer

Abstract: This article presents the possibility of extending the service life of XLPE insulation based on high voltage cables by blending the optimum concentration of the aromatic voltage stabilizer. The insulation performance of XLPE is analyzed by adding the 0.5, 1, and 3 wt% of 3‐aminobenzoic acid voltage stabilizer. The investigated insulation properties include the DC step‐by‐step breakdown to estimate the life exponent, space charge, DC conductivity, surface potential decay, dielectric loss, and dielectric constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Moreover, as shown in Figure 7 a, the melting peak temperature decreases gradually with the increase of DCP content. According to the Thomson-Gibbs equation, the thickness of lamellae for polyethylene can be calculated as follows: L = 2 σT m 0 /(Δ H v *( T m 0 − T m )) where L is the thickness of lamella in nm, σ is the lamellar surface free energy (0.07 J·m −2 ), T 0 m is equilibrium melting point of polyethylene (414.5 K), and Δ H v is the melting enthalpy of lamella with infinite thickness for polyethylene (2.88 × 10 8 J·m −3 ) [ 21 , 24 ], and T m is the measured melting peak point of samples in K. Therefore, a lower melting peak temperature corresponds to a thinner lamella, and the decrease of melting peak temperature with the increase of DCP content indicates that lamellae of composites tend to decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as shown in Figure 7 a, the melting peak temperature decreases gradually with the increase of DCP content. According to the Thomson-Gibbs equation, the thickness of lamellae for polyethylene can be calculated as follows: L = 2 σT m 0 /(Δ H v *( T m 0 − T m )) where L is the thickness of lamella in nm, σ is the lamellar surface free energy (0.07 J·m −2 ), T 0 m is equilibrium melting point of polyethylene (414.5 K), and Δ H v is the melting enthalpy of lamella with infinite thickness for polyethylene (2.88 × 10 8 J·m −3 ) [ 21 , 24 ], and T m is the measured melting peak point of samples in K. Therefore, a lower melting peak temperature corresponds to a thinner lamella, and the decrease of melting peak temperature with the increase of DCP content indicates that lamellae of composites tend to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…where L is the thickness of lamella in nm, σ is the lamellar surface free energy (0.07 J•m −2 ), T 0 m is equilibrium melting point of polyethylene (414.5 K), and ∆H v is the melting enthalpy of lamella with infinite thickness for polyethylene (2.88 × 10 8 J•m −3 ) [21,24], and T m is the measured melting peak point of samples in K. Therefore, a lower melting peak temperature corresponds to a thinner lamella, and the decrease of melting peak temperature with the increase of DCP content indicates that lamellae of composites tend to decrease. As for crystallization process of composites, two peaks could be observed, shown in Figure 7b.…”
Section: Degree Of Crosslinking and Crystallinitymentioning
confidence: 99%
“…The insulating characteristics of cross‐linked polyethylene (XLPE) was investigated using different amount of 3‐aminobenzoic acid voltage stabilizer 18 . It was shown that 1 wt% added stabilizer had drastically increased the life exponent (10 to 15), thermal stability, and melting properties; whereas, the dc conductivity, dielectric constant, and dielectric loss were reduced compared to base polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The space charge distribution test of LDPE and LDPE/polypyrrole nanocomposites was carried out by pulse electro‐acoustic method, [ 17, 18 ] and silicone oil was used as acoustic coupling agent. The specimen with the thickness of about 300 μm was applied to a −40 kV/mm electric field for 40 min, and the space charge distributions at 1, 10, 20, 30, and 40 min were recorded.…”
Section: Methodsmentioning
confidence: 99%